A new approximation for a general shear inviscid flow past a circle. (1st January 2014) - Dériat, Emmanuel
This paper deals with 2D, inviscid, incompressible and rotational flows perturbed by a circle and Joukowski profiles. A new approximation of the streamfunction corresponding to a perturbed parabolic velocity profile is given and compared with Nagamatsu approximated solution. Our solution is better in the sense that the rotational is kept zero on the body since it is zero on the streamline coming from the infinity and leading to the front stagnation point; it is nevertheless an approximation because the vortex is not conserved on other 'streamlines' except at infinity. The concept of generalised complex velocity potential, is given.